Eficiência na arrecadação de tributos: análise através de uma fronteira estocástica de custo aplicada as delegacias da Receita Federal do Brasil - Souza, Fernando Augusto Carvalho de (2011)
This study aims to evaluate the performance of Police Internal Revenue through the establishment of an efficient frontier based on parametric cost, using such a stochastic model that splits the noise into two components, one random and one from the inefficiency of each unit . The work will be based on data for the years 2006 and 2008 in a cross section. and aims to assess the public policy of unification of state agencies responsible for tax collection at the Federal level, the Internal Revenue Service with the Federal Social Security, held by the Law 11,457 of March 16, 2007. The main goal of research is to determine if the decentralized units of the Internal Revenue Service, notably the Internal Revenue Offices are operating efficiently, the task of collecting taxes, depending on the resources made available so implementation of its activities. In this research unit of the product to be evaluated is the collection, among the many activities undertaken by the agency, in providing the state action to implement public policy. The conclusion suggests that the regions where a large number of companies opting for tax rules for SIMPLES, as well as those who hold in their companies considered DIFFERENTIATED jurisdiction of its size, resulting in an increase in the cost of Police. The units that are the capitals of the states have improved their performance after the unification. Furthermore, a greater proportion of Fiscal Auditors within the precinct in relation to all servers reduces inefficiency. The work is expected to contribute in the evaluation of this new management model implemented in the federal tax administration in the country.